Interpretasi Paham Radikalisme Pascabom di Surabaya dalam Perspektif Historis - Eko Setiawan (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2019)
The humanitarian tragedy through a series of bombings carried out by one family, such as a willingness to be disguised for their actions as not to seek an attention, and the use of children in the acts of terrorism tosacrifice all family members, this has never happened in any part of the world which have swallowed recent casualties and property losses occurred in Surabaya, became a highlight for all Indonesian people and the world as well. The growth of radicalism eventually shows the face of violence in Indonesia, this terrorism movement is intended as a form of resistance, in carrying out its actions solely as a jihad to uphold the truth they believe in. The basis and purpose of their foundation is religion, but the religion which is narrowly understood and packaged in such a way becomes a radical ideology of resistance. It does not mean that terrorist activists of jihad are lack of education, some of them are smart people but they are frustrated by the socio-political hegemony of secularhedonic culture. Terror is still one of the ways to express radicalism, aterror which is motivated by religious ideology and dissatisfaction, is very dangerous due to an excessive individual fanaticism and willingness to sacrifice oneself in achieving the goals.